The Reform of Wholesale Payment Systems and its Impacton Financial Markets - Schoenmaker, Dirk (IMF Working Papers; Working Paper ;, 1996)
This paper reviews the ongoing efforts to reduce the risks inherent in the world's principal wholesale payment systems. The paper assesses the major policy proposals to contain the growth in intraday credit exposures that arises in net settlement wholesale payment systems and in the real-time gross systems in which the central bank provides daylight overdrafts. It also discusses the benefits of these risk-management policies, and we assess the adverse impact of applying interest charges for intraday central-bank credit or of collateralizing such credit on liquidity in financial markets.